2018
DOI: 10.3390/cryst8120473
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Mechanical, and Dynamical Properties of Amorphous Li2CO3 from Molecular Dynamics Simulations

Abstract: Structural, mechanical, and transport properties of amorphous Li2CO3 were studied using molecular dynamics (MD) simulations and a hybrid MD-Monte Carlo (MC) scheme. A many-body polarizable force field (APPLE&P) was employed in all simulations. Dynamic and mechanical properties of Dilithium carbonate, Li2CO3, in amorphous liquid and glassy phases were calculated over a wide temperature range. At higher temperatures, both anion and cation diffusion coefficients showed similar temperature dependence. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Instead, the sizes of pores are 5–10 nm, which are equal to or greater than those of Li 2 CO 3 nanoparticles (∼5 nm) in Figure b. Previous investigations have shown that the crystalline Li 2 CO 3 has a little higher diffusivity and ionic conductivity than the amorphous phase. Thus, the amorphous Li 2 CO 3 may provide charge-transport channels for the delithiation and charge-transfer process, inducing the preferential decomposition of crystal nanoparticles. These nanopores indicate that the crystalline Li 2 CO 3 nanoparticles are consumed and the amorphous region also contributes to being excavated upon charge.…”
Section: Resultsmentioning
confidence: 86%
“…Instead, the sizes of pores are 5–10 nm, which are equal to or greater than those of Li 2 CO 3 nanoparticles (∼5 nm) in Figure b. Previous investigations have shown that the crystalline Li 2 CO 3 has a little higher diffusivity and ionic conductivity than the amorphous phase. Thus, the amorphous Li 2 CO 3 may provide charge-transport channels for the delithiation and charge-transfer process, inducing the preferential decomposition of crystal nanoparticles. These nanopores indicate that the crystalline Li 2 CO 3 nanoparticles are consumed and the amorphous region also contributes to being excavated upon charge.…”
Section: Resultsmentioning
confidence: 86%
“…55 Li 2 CO 3 has much poorer Li conductivity (∼10 −3 mS/cm) at room temperature compared to LLZO. 56 There is a large difference in interfacial resistances of the sample that only contains Li 2 CO 3 after exposure to 500 °C and that of the sample that contains Li 2 CO 3 , La 2 Zr 2 O 7 , and La(Ni,Co)O 3 after exposure to 700 °C. The interfacial resistance found from the former was 2.1 kΩ cm 2 and that from the latter was 102 kΩ cm 2 .…”
Section: Discussionmentioning
confidence: 97%
“…There are perovskite Li conductors such as (Li,La)­TiO 3 , but Li conduction requires substantial A-site vacancy fraction . Li 2 CO 3 has much poorer Li conductivity (∼10 –3 mS/cm) at room temperature compared to LLZO …”
Section: Discussionmentioning
confidence: 99%
“…Li 2 CO 3 has limited Li‐ion conductivity (10 −3 mS cm −1 ) at room temperature, much lower compared to that in LLZO. [ 91 ] La 2 Zr 2 O 7 and Ruddelsden‐popper phases are also not Li‐ion conductors. [ 27,92 ] We do not expect carbonated species (La 2 O 2 CO 3 , NiCO 3 , and CoCO 3 ) to have good Li‐ion conductivities since they do not have Li in their lattice nor cation vacancy channel for lithium ion transport.…”
Section: Discussionmentioning
confidence: 99%